An immunohistochemical study of pancreatic endocrine cells in SKH-1 hairless mice - Ku, SK; Lee, HS; Lee, JH (European Journal of Histochemistry, 2010)
The regional distribution and frequency of the pancreatic endocrine cells in the SKH-1 hairless mouse were studied by an immunohistochemical (peroxidase anti-peroxidase; PAP) method using four types of specific antisera against insulin, glucagon, somatostatin and human pancreatic polypeptide (PP). The pancreas of mice were divided into three portions; pancreatic islets, exocrine and pancreatic ducts. The pancreatic islets were further subdivided into three regions (central, mantle and peripheral region) according to their located types of immunoreactive cells. In the pancreatic islet portions, insulin-immunoreactive cells were located in the central and mantle regions with 84.60 ± 7.65 and 33.00 ± 12.45/100 cells frequencies, respectively, but most of somatostatin-, glucagon- and PPimmunoreactive cells were detected in the mantle and peripheral regions. In the mantle region, somatostatin-, glucagon- and PP-immunoreactive cells were demonstrated with 28.70 ± 9.91, 52.00 ± 14.05 and 2.60 ± 1.51/100 cells frequencies, respectively, and showed 6.20 ± 2.86, 15.30 ± 5.31 and 21.50 ± 10.28/100 cells frequencies, respectively in peripheral regions. However, glucagon-immunoreactive cells were also demonstrated in the central regions with 4.00 ± 2.83/100 cells frequency. In the exocrine portions, insulin-, glucagon-, somatostatin- and PPimmunoreactive cells were demonstrated in the SKH-1 mouse with 0.90 ± 0.74, 0.80 ± 0.79, 4.90 ± 3.54 and 2.70 ± 1.34/100 cells frequencies, respectively. In the pancreatic duct portions, insulin-, glucagon- and somatostatin-immunoreactive cells were demonstrated in the subepithelial connective tissues and showed islet-like appearances with 30.30 ± 14.67, 2.70 ± 3.13 and 5.90 ± 4.23/100 cells frequencies, respectively. However, no PP-immunoreactive cells were demonstrated in these regions. In conclusion, some peculiar distributional patterns of pancreatic endocrine cells were found in the SKH-1 hairless mouse.